PENINGKATAN HASIL BELAJAR SATUAN WAKTU DENGAN MODEL COOVERATIVE LEARNING TIPE NUMBERED HEAD TOGETHER DI SD - Pratiwi, Vani Okza (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research was motivated by the learning unit count operations during this time that learning is centered on teachers. To follow up on this issue a step that can be used with NHT model of cooperative learning style. This research is action research, this study used qualitative and quantitative approaches. assessment of student learning outcomes in the first cycle in the cognitive, affective, and psychomotor obtained an average value of 64.65%, an increase in cycle II with an average of 87.33%.   Kata Kunci: satuan waktu, numbered head together